Sistem Pakar Penentuan Tipe Kepribadian Siswa Sekolah Dasar Menggunakan Metode Case Based Reasoning - Roki Hardianto (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
Determination of the personality of elementary school students with Case Based Reasoning method is an activity to map student behavior in school so that student mischief can be directed into something that can support student's success in learning and teaching process. With Case Based Reasoning is a method of searching in a regular system of experts and widely used psychological problem calculations. In this method there are 4 stages namely Retrieve, Reuse, Revise, and Retain. Because primary school in its special area is very far from the primary school in the city on the sensitivity of the principal's head evaluates the learning process of the students and the desired learning according to the character of the students. Keywords : Expert System, Personality, Case Based Reasoning